News in Brief - Lagos Araujo, Leslie Kelly (2012)
This section contains a small compilation of news and events that took place in Peru and that are interesting from a chemistry perspective. You will see that Chemistry is present in almost everything in our everyday life. This 2012 issue features news related to the L’Oreal-Unesco Prize awarded to a Chemistry Professor from PUCP, the increased demand for engineers and scientists in Peru to improve scientific research in the country, the classification of the diesel fuel as carcinogenic by the WHO, the new list of controlled chemical substances by the SUNAT, news related with the export of chemicals from Peru and many more news.